Analisis Strategi Bersaing Pasar Kaget untuk Memenangkan Persaingan - Purwanto Purwanto; Anaconda Bangkara (Forum Manajemen Indonesia (FMI), 2016)
The problem companies are becoming increasingly complex and competitive business be increased very sharply, as a result of changes in the business environment in the era of globalization. Companies must be able to adapt to the environment in order to survive in the midst of these conditions. For that management is required to manage the organization in a better and more professional in controlling the activities of the company. Business